2013
DOI: 10.1128/jb.01372-13
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Direct HetR Regulon in Anabaena sp. Strain PCC 7120

Abstract: In response to a lack of environmental combined nitrogen, the filamentous cyanobacterium Anabaena sp. strain PCC 7120 differentiates nitrogen-fixing heterocyst cells in a periodic pattern. HetR is a transcription factor that coordinates the regulation of this developmental program. An inverted repeat-containing sequence in the hepA promoter required for proheterocyst-specific transcription was identified based on sequence similarity to a previously characterized binding site for HetR in the promoter of hetP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 52 publications
0
51
0
Order By: Relevance
“…2) causes great reduction in interaction with HetR. It is notable that although Videau et al [19] found no binding of recombinant HetR to the hetR site in EMSA and Flaherty et al [16] found no binding of GST-HetR to the patA site in vitro, we observed clear band shifts in EMSA, showing that EF-Ts-HetR bound to those sites. We suggest that the EF-Ts-HetR fusion that we used was likely more active than the refolded recombinant HetR or the GST-HetR fusion used by the other two laboratories, because EF-Ts greatly enhances the solubility of overexpressed proteins in E. coli [25].…”
Section: Discussionmentioning
confidence: 36%
See 4 more Smart Citations
“…2) causes great reduction in interaction with HetR. It is notable that although Videau et al [19] found no binding of recombinant HetR to the hetR site in EMSA and Flaherty et al [16] found no binding of GST-HetR to the patA site in vitro, we observed clear band shifts in EMSA, showing that EF-Ts-HetR bound to those sites. We suggest that the EF-Ts-HetR fusion that we used was likely more active than the refolded recombinant HetR or the GST-HetR fusion used by the other two laboratories, because EF-Ts greatly enhances the solubility of overexpressed proteins in E. coli [25].…”
Section: Discussionmentioning
confidence: 36%
“…In addition, the binding of HetR to another predicted site, the one upstream of hepA [10], was confirmed and shown to be much weaker than that to the hetZ site ( Fig. S1) as reported [19]. EF-Ts-HetR (2 or 4 lmol/L) was then used to bind 40-bp fragments P hetP -40, P hetZ -40, P hetR -40 and P patA -40, respectively, with or without RGSGR, the pentapeptide inhibitor of HetR [2,10] (Fig.…”
mentioning
confidence: 51%
See 3 more Smart Citations